2023
DOI: 10.1021/acs.analchem.2c05511
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Quantifying Microdroplet Synthesis of Metal–Organic Framework Colloids Using Gas-Phase Electrophoresis

Abstract: A hyphenated electrospray-differential mobility analysis (ES-DMA) was developed for providing a high-resolution, real-time quantitative analysis on the metal−organic framework (MOF) colloids produced via the concept of microfluidic flow chemistry. Zeolitic imidazolate framework-8 was chosen as the representative MOF of the study. The results show that the physical size and number concentration of the MOF colloid were successfully characterized by the hyphenated ES-DMA during the microdroplet synthetic process,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Higher temperature also accelerated the surface growth rate, resulting in the generation of large-sized (micrometer-scale) MOF-74-Co, which was consistent with previous reports. 53,54 Considering the effect of reaction temperature on particle sizes and the low energy consumption of the synthesis process, MOF-74-Co was prepared at room temperature (25 °C).…”
Section: Water-based Preparation Of Mof-74-co By High-gravity Technologymentioning
confidence: 99%
“…Higher temperature also accelerated the surface growth rate, resulting in the generation of large-sized (micrometer-scale) MOF-74-Co, which was consistent with previous reports. 53,54 Considering the effect of reaction temperature on particle sizes and the low energy consumption of the synthesis process, MOF-74-Co was prepared at room temperature (25 °C).…”
Section: Water-based Preparation Of Mof-74-co By High-gravity Technologymentioning
confidence: 99%
“…5 For droplet generation two immiscible fluids are injected into a microchannel to generate isolated volumes of liquids in a precise and controlled manner at kilo-hertz rates, 6,7 eliminating cross-contamination, dispersion, and sample dilution within the droplets. [8][9][10] For the reasons mentioned above, droplet microfluidic/ microreactor has become a major focus in the fabrication of micromaterials and nanomaterials with various morphologies, 11 such as microbubbles, 12 hollow polymeric microcapsules, 13 double emulsions, 14 extracellular vesicles, 15 and Janus particles. 16 Additionally, nanoparticles (NPs) of CdSe, 4 cesium lead halide perovskite, 17 and gold 18 have been successfully fabricated inside moving droplets.…”
Section: Introductionmentioning
confidence: 99%
“…5 For droplet generation two immiscible fluids are injected into a microchannel to generate isolated volumes of liquids in a precise and controlled manner at kilohertz rates, 6,7 eliminating cross-contamination, dispersion, and sample dilution within the droplets. 8–10…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, it is equally important to establish a real‐time analytical system for the continuously synthesized MOFs and MOF‐derived products so that explicit knowledge of the effect of reaction parameters on the synthesized products can be obtained. [ 48 ] Previous studies have already reported that the electrospray‐differential mobility analysis (ES‐DMA) system can be used to quantitatively analyze the synthetic conditions, stability, and size properties of the colloidal products by evaluating their corresponding mobility diameter distributions obtained from ES‐DMA. [ 49–52 ] Based on this, we have recently developed an ES‐DMA‐based system for the real‐time analysis of the continuously produced MOF products through microdroplet synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 49–52 ] Based on this, we have recently developed an ES‐DMA‐based system for the real‐time analysis of the continuously produced MOF products through microdroplet synthesis. [ 48 ] However, no such analytical system is constructed for the real‐time analysis of the continuously produced MOF‐derived products.…”
Section: Introductionmentioning
confidence: 99%